2020
DOI: 10.31235/osf.io/b7cjp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What factors predict the self-identification of drug dependency among criminal justice populations? Prevalence, correlates, and implications for the criminal justice system

Abstract: The drug-crime nexus has long received international interest from both drug-crime scholars and public policy experts worldwide. While there is little disagreement that more frequent drug use is linked to higher rates of crime the causal underpinnings of this relationship remain hotly contested. One area of increasing interest among criminological, social, and psychological scholars alike is the confounding influence and power of 'identity' in shaping the long-term behavioural trajectories of both drug use and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…In a study of a more than 14,000 recent drug-using police detainees in Australia it was shown that 53 percent self-identified as drug dependent (Langfield and Payne, 2020). In that paper, the authors noted several problems with the criminal justice system's reliance on self-attribution as a gateway to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of a more than 14,000 recent drug-using police detainees in Australia it was shown that 53 percent self-identified as drug dependent (Langfield and Payne, 2020). In that paper, the authors noted several problems with the criminal justice system's reliance on self-attribution as a gateway to treatment.…”
Section: Introductionmentioning
confidence: 99%